(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Tillage practices constitute the major initial applications of farm power and machinery during crop cultivation. They comprise all soil-related manipulations aimed at preparing a good seedbed for appropriate crop growth. In order to improve crop yields while enabling sustainable soils, tillage practices executed during crop production in a particular region need to be assessed. The aim of this study was to investigate the impacts of tillage practices on Alexander wander wheat growth, and yield in Bamenda, Cameroon. An experiment was conducted during the cropping seasons of 2023 and 2024 at the research farm of the College of Technology of the University of Bamenda, Cameroon laid out in a randomized complete block design comprising five tillage treatments namely; mechanized tillage (disc ploughing followed by disc harrowing), conservation tillage (no-tillage, and strip tillage), and small-scale tillage (burning in ridges (“Ankara”), and traditional ridge tillage). Disc ploughing was conducted using a 3-disc standard right-handed disc plough followed by disc harrowing using an offset disc harrow. Tillage significantly influenced wheat performance (growth parameters, and yield attributes) during both the 2023, and 2024 cropping seasons. Ankara produced the best wheat performance followed by traditional ridge tillage. Disc ploughing followed by disc harrowing came third, while no-tillage, and strip-tillage practices produced the poorest wheat growth parameters, and yield attributes during both years. Thus, small-scale tillage practices (Ankara and traditional ridge tillage) are recommended for Alexander wander wheat production in Bamenda, Cameroon followed by mechanized tillage (disc ploughing followed by disc harrowing). Int. J. Agril. Res. Innov. Tech. 14(2): 20-27, December 2024